The Calcineurin Inhibitor FK506 Prevents Cognitive Impairment by Inhibiting Reactive Astrogliosis in Pilocarpine-Induced Status Epilepticus Rats - Liu, Jinzhi; Si, Zhihua; Li, Shuqing; Huang, Zhan; He, Yan; Zhang, Tao; Wang, Aihua (Frontiers in Cellular Neuroscience, 2018)
Status epilepticus (SE) is a severe clinical manifestation of epilepsy accompanying with cognitive impairment and brain damage. Astrocyte activation occurs following seizures and plays an important role in epilepsy-induced pathological injury, including cognitive impairment. FK506, an immunosuppressant used in clinical settings to prevent allograft rejection, has been shown to exhibit neuroprotective effects in central nervous system diseases. The present study was designed to investigate the effect of FK506 on cognitive impairment in a lithium-pilocarpine-induced SE rat model. It’s found that FK506 treatment significantly increased the latency period to seizures and decreased the maximal intensity of seizures. FK506 treatment also markedly increased the surviving cells and reduced the neuron apoptosis after seizures. Meanwhile, FK506 treatment reduced the escape latency and prolonged the swimming distance in the Morris water maze test. In addition, FK506 treatment down-regulated the expression level of GFAP, a speciﬁc marker of astrocytes. In conclusion, FK506 could prevent and recover cognitive impairment by inhibiting reactive astrogliosis in pilocarpine-induced status epilepticus rats, suggesting that FK506 may be a promising agent for the treatment of epilepsy.